Increased Excitability Induced in the Primary Motor Cortex by Transcranial Ultrasound Stimulation - Gibson, Benjamin C.; Sanguinetti, Joseph L.; Badran, Bashar W.; Yu, Alfred B.; Klein, Evan P.; Abbott, Christopher C.; Hansberger, Jeffrey T.; Clark, Vincent P. (Frontiers in Neurology, 2018)
Background: Transcranial Ultrasound Stimulation (tUS) is an emerging technique that uses ultrasonic waves to noninvasively modulate brain activity. As with other forms of non-invasive brain stimulation (NIBS), tUS may be useful for altering cortical excitability and neuroplasticity for a variety of research and clinical applications. The effects of tUS on cortical excitability are still unclear, and further complications arise from the wide parameter space offered by various types of devices, transducer arrangements, and stimulation protocols. Diagnostic ultrasound imaging devices are safe, readily available systems that may be useful for tUS. However, the feasibility of modifying brain activity with diagnostic tUS is currently unknown. Objective: We aimed to examine the effects of a commercial diagnostic tUS device using an imaging protocol on cortical excitability. We hypothesized that imaging tUS applied to motor cortex could induce changes in cortical excitability as measured using a transcranial magnetic stimulation (TMS) motor evoked potential (MEP) paradigm. Methods: Forty-three subjects were assigned to receive either verum (n=21) or sham (n=22) diagnostic tUS in a single-blind design. Baseline motor cortex excitability was measured using MEPs elicited by TMS. Diagnostic tUS was subsequently administered to the same cortical area for 2 minutes, immediately followed by repeated post-stimulation MEPs recorded up to 16 minutes post-stimulation. Results: Verum tUS increased cortical excitability (from baseline) by 33.7% immediately following tUS (p = 0.009), and 32.4% (p = 0.047) 6 minutes later, with excitability no longer significantly different from baseline by 11 minutes post-stimulation. By contrast, subjects receiving sham tUS showed no significant changes in MEP amplitude. Conclusion: These findings demonstrate that tUS delivered via a commercially available diagnostic imaging ultrasound system transiently increases excitability in the motor cortex as measured by MEPs. Diagnostic tUS devices are readily available, and the present results suggest that they may offer a promising tool for noninvasively modulating activity in the central nervous system. Further studies exploring the use of diagnostic imaging devices for neuromodulation are warranted.